A bear called Paddington - Bond, Michael; Fortnum, Peggy (New York : Dell, 1958)
A very small bear found by Mr. and Mrs. Brown at Paddington Station becomes one of the family.
"Yearling book.".
Keywords: Bears -- Fiction; Bears -- Fiction